Foraging behaviour of Magellanic Penguins during the early chick-rearing period at Isla de los Estados, Argentina - Rosciano, Natalia Gimena; Pütz, Klemens; Polito, Michael J.; Raya Rey, Andrea Nélida (Ibis)
Studies of the at-sea distribution and trophic ecology of penguins are essential to understand their role in the broader marine food web. Magellanic Penguins Spheniscus magellanicus have a wide distribution and their foraging behaviour varies across breeding sites and between sexes, among others. In this study, we characterized the at-sea areas, the diving strategies and the relative trophic level of Magellanic Penguins breeding at Isla de los Estados, Argentina, during the early chick-rearing period. In addition, we quantified the interannual, sexual and individual variability in those parameters during three breeding seasons (2011–2013) using devices recording position and dive depth, and obtained blood samples for stable isotope analysis. During the early chick-rearing period, Magellanic Penguins showed small differences between the sexes in their foraging behaviour and large overlap in the at-sea areas used, suggesting no intraspecific variation between sexes. Although there was interannual variability in the foraging behaviour and the trophic level of the penguins, most of the studied nests managed successfully to raise both chicks during the first stage of the breeding cycle (guard stage). The foraging ecology of Magellanic Penguins from this colony was comparable with results of past studies at other breeding colonies. This study contributes to the identification of important at-sea areas for Magellanic Penguins at the southern edge of their distribution and also to the identification of possible threats in the study area such as interaction with fisheries. Fil: Rosciano, Natalia Gimena. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Pütz, Klemens. Antarctic Research Trust; Alemania Fil: Polito, Michael J. State University of Louisiana; Estados Unidos Fil: Raya Rey, Andrea Nélida. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina